Cartography of Suicide-Related Health Indicators and Suicide Attempts in Morocco - Latifa Amiar; Rachida Soulaymani-Bencheikh; Faical El Hattimy; Hinde Hami; Ahmed Aarab; Abderrazak Khadmaoui; Abdelmajid Soulaymani (European Scientific Journal, ESJ, 2018)
The present work consists of a retrospective study of suicidal intoxication during a period stretching from January 1980 to December 2013, reported to the Poison Control and Pharmaco-vigilance Center of Morocco through two systems of data collection: Toxicological Information and Toxico-vigilance. The objective is to determine the spatio-temporal evolution of the incidence, lethality and mortality related to suicides and suicide attempts through intoxication in Morocco. During the study period, the average annual number of suicidal intoxications was 707 cases. All regions of Morocco have been affected but at variable rates. The average age of the victims is 24.39 ± 0.08 years, with a sex ratio of 2.41 in favor of the female sex. In the space of 34 years, the incidence is 2.4 per 100,000 inhabitants, the mortality is 0.67 per million inhabitants and the lethality is 0.08%. The annual increase in biological indicators makes suicides and suicide attempts a public health problem, through hospital care and the resulting socio-economic and psychological consequences. This problem seems much more common in urban areas and particularly in the big cities of Morocco.